The Effect of Zikir Manaqib Sheikh Abdul Qadir al-Jailani on the Peace of Mind of Congregation at the Salafi Miftahul Huda Islamic Boarding School Jatake Tangerang Banten - Putri Auliani; Alfadhli Alfadhli (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to explore and reveal the implementation of zikir manaqib at the Salafi Miftahul Huda Islamic Boarding School in Jatake, Tangerang Regency and its effect on the peace of mind of the congregation at the Salafi Miftahul Huda Islamic Boarding School in Jatake, Tangerang Regency. This research is field research with a quantitative descriptive approach, namely analyzing data in the form of numbers with the aim of finding the influence between two or more variables with a population of around 1000 people who are congregants at the Salafi Miftahul Huda Jatake Islamic Boarding School, Tangerang Regency. The sampling technique used is simple random sampling, namely random sampling that does not see the strata that exist in members of a population with a sample of 91 people consisting of 52 men and 39 women aged 11 to 50 years and over who are taken randomly. The research instrument used a questionnaire sheet and statistical tests using simple linear regression which aims to determine how much influence the X variable has on the Y variable. The results showed that the significance value (0.000) is less than the p-value (significance value <0.05) so that the regression model can be used to predict the effect of variable X (Zikir Manaqib) with variable Y (peace of mind) or H1 is accepted. The results of the calculation of the coefficient of determination or R square value of 0.417 are converted to percent form to 41.7%, this percentage has shown the influence of variable X (Zikir Manaqib) on variable Y (peace of mind). Thus it can be concluded that there is an influence of Zikir Manaqib on the peace of mind of the congregation at the Miftahul Huda Salafi Islamic Boarding School in Jatake, Tangerang Regency.